Construction of Smart Home System Architecture for Operating - Jianting Han (Dianxin kexue)
With the development of the terminal and broadband network technology,smart home related services have been developed rapidly.The latest development of the smart home applications and related home network technology trends were analyzed firstly,and the key elements of the operating services of the smart home were demonstrated.On this basis,the system architecture of the operators to build smart home services was presented,and the related key technologies involved were analyzed,and the feasibility of the system was verified.